Eupelops plicatus - Murvanidze, Maka; Cilbircioğlu, Cihan; Özdemir, Esengül; Inak, Emre (Zenodo, 2020)
Eupelops plicatus (C.L. Koch, 1835) * Material – New record for Turkey. One specimen in Ankara university campus, N 39° 96′ 35.51′′, E 32° 86′ 11.78′′, alt. = 858 m, 25 July 2018, mushrooms. Global distribution – Holarctic. Ecology – All types of habitats. Remarks – Measurements: The size of Turkish specimen (500 × 345 µm) is at the lower range provided in the literature (Weigmann 2006). All characters match previous descriptions (Ghilarov and Krivolutsky 1975; Beck and Woas 1991; Weigmann 2006).

Published as part of Murvanidze, Maka, Cilbircioğlu, Cihan, Özdemir, Esengül & Inak, Emre, 2020, Checklist of oribatid mites (Acari: Oribatida) of the Central Black Sea basin of Turkey with new records for the country, pp. 255-277 in Persian Journal of Acarology 9 (3) on page 263, DOI: 10.22073/pja.v9i3.61909, http://zenodo.org/record/5236444
Keywords: Arthropoda; Arachnida; Animalia; Eupelops; Eupelops plicatus; Biodiversity; Sarcoptiformes; Phenopelopidae; Taxonomy; 14. Life underwater